2020
DOI: 10.1002/ijfe.2298
|View full text |Cite
|
Sign up to set email alerts
|

The pandemic and economic policy uncertainty

Abstract: The events that occurred after the worldwide diffusion of COVID‐19 provide a real‐life example of how uncertainty can severely affect the global economy. This paper reviews literature on the negative impacts of the economic policy uncertainty index (EPU) as developed by Baker et al., The Quarterly Journal of Economics, 2016, 131, 1593–1636 on individuals, businesses, governments, and economies at the local and international levels. This reveals that a high EPU is associated with adverse effects on households, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 109 publications
0
49
0
2
Order By: Relevance
“…They also note that the effects of political and regulatory uncertainty extend even to the commodity and crypto-currency markets. [ 61 ]. Song and Zhou also acknowledge the fact that uncertainty plays a key role in the current economic crisis.…”
Section: Discussionmentioning
confidence: 99%
“…They also note that the effects of political and regulatory uncertainty extend even to the commodity and crypto-currency markets. [ 61 ]. Song and Zhou also acknowledge the fact that uncertainty plays a key role in the current economic crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies further explored these issues, but reported different views and opinions. Many economists have shown that increased uncertainty causes rms to reduce investment, bond issuance, and spending (Al-Thaqeb et al 2020) so that innovation stalls in the form of R&D spending and new product development (Shankar 2020). Moreover, studies have also speculated that policy uncertainty will detrimentally affect economic innovation power through innovation quantity, quality, and risk by verifying the theoretical models of 43 countries (Bhattacharya et al 2017).…”
Section: Economic Policy Uncertainty and Green Technology Innovatiomentioning
confidence: 98%
“…Specifically, the business lockdowns and extensive medical and health expenditures have caused enormous economic losses [48] , [49] , resulting in the risk of government debt and so the fiscal deficit. According to International Monetary Fund (IMF), the global fiscal deficit as a share of GDP might rise from 3.7% in 2019 to 9.9% in 2020, while the percentage of public debt in developed economies would rise from 105% to 122% of GDP [50] .…”
Section: Energy Transition During Covid-19mentioning
confidence: 99%